Inquiry-Based Learning in Action: Perspectives from International Baccalaureate Mathematics Classrooms - Christian L. Salazar; Razil M. Gumanoy (Universitas Sriwijaya, 2025)
Despite the widespread adoption of inquiry-based learning (IBL) in mathematics education to enhance critical thinking and problem-solving, significant challenges continue to hinder its intended impact, further exacerbating the issue and underscoring the urgent need for in-depth analysis. This study explores the influence of IBL approaches using a phenomenology. Participants included six mathematics teachers, ten students, and seven school administrators who participated in focus group discussions. Essential themes emerged around pedagogical strategies, classroom practices, challenges, and contextual factors, highlighting the complex interplay between inquiry-based learning implementation, teacher facilitation, curriculum demands, and the institutional dynamics of IB Mathematics classrooms.